PENGEMBANGAN DESAIN WEBSITE SEBAGAI MEDIA INFORMAS DAN PROMOSI (Studi Kasus: PT.Nada Surya Tunggal Kecamatan Pringapus) - Daniel Rudjiono; Heru Saputro (STEKOM PRESS, 2020)
PT. Nada Surya Tunggal is a company engaged in the textile sector, which is located at JL. Raya Candirejo, Pringapus, Kab. Semarang 50552, Central Java. The problems that occurred at PT. Nada Surya Tunggal is the lack of knowledge of local and foreign people about the types of products produced by the company due to the lack of maximum promotional media used so that the marketing department is required to have many relationships so that the marketing process is slower. People find it difficult to know about several things such as the shape or visual of the product, product design, and the materials or materials used for production. This causes confusion in the community about product specifications which results in a lack of public interest in buying.This research is a type of development research that uses the Research and Development (R&D) method. Meanwhile, for making your own website design using the programming languages HTML, CSS, and Javascript. With the new website design owned by PT. Nada Surya Tunggal can expand its marketing reach without incurring higher costs, the promotion process is faster, the public is more interested and comfortable to access, as well as the products owned by PT. Nada Surya Tunggal is becoming better known by the wider community.